Sonifying the brightness of the stars - Sánchez González, Javier; Dominguez , Santiago Vargas (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Sonification is the use of voiceless audio to convey information and can be used to support inclusiveastronomy, in particular to develop initiatives to get closer to the wonders of the universe and createaccessible content for visually impaired audiences. In this work we present the design and implementationof a device to soundly reproduce the brightness of stars, converting light into audible sounds. The deviceconsists of a light sensor, a 16-bit digital analog converter, and an arduino. The sensor can be installed in theeyepiece of a telescope to acquire the light data, thus obtaining a sound as output, with different frequenciesdepending on the apparent magnitude of the star that the instrument looks at.